Quality of life in patients with fibromyalgia syndrome and rheumatoid arthritis - (:unkn) unknown (SPRINGER, 2005)
The objective of this study was to determine and compare the quality of life (QOL) of patients with fibromyalgia syndrome (FS) and rheumatoid arthritis (RA) and to assess patients' psychological and functional status in each group. This prospective study included 62 female FS patients and 60 female RA patients diagnosed by the American College of Rheumatology criteria. The Turkish translations of the Arthritis Impact Measurement Scale II (AIMS II) and Beck Depression Index (BDI) were given to all of the patients and they were asked to complete the two questionnaires. The scores of AIMS II, pain, and QOL were evaluated in the FS and RA groups. There were no statistically significant differences between the FS and RA groups (p > 0.05) in terms of QOL. The affect subgroup scores of the AIMS II and BDI were highly correlated in the FS and RA groups) < 0.002, r = 0.85 and p < 0.05, r = 0.80, respectively). The results show that the QOL is negatively but similarly affected in FS and RA groups.
Keywords: AIMS II; Beck Depression Index; Fibromyalgia syndrome; quality of life; rheumatoid arthritis; IMPACT QUESTIONNAIRE; HEALTH-STATUS; CLASSIFICATION; VALIDATION; CRITERIA; VERSION